Geoff Eley: society, politics and ideology in German historiography (1974-1984) - Olivera, Gastón Alejandro (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
The aim of this paper is to describe British Geoff Eley (born in 1949) intellectual development as an account to understand current debates about his discipline. Focusing on his experience and practice in the historiographic field as a German historian. To achieve the previous idea, this paper considers his early productions, from his doctoral thesis first introduced in 1974- still a rare piece of writing- going through a series of critical analysis mentioned on specialized magazines during the second half of that decade to his masterpiece published in 1980 and later on expanded in the British edition of 1984. This case study allows recognizing in first person the way how a training historian dealt with problems inside social history, in the methodological aspect as well as the conceptual one, particularly at a moment in which social history gain status in western countries as the new historiographic paradigm. Our hypothesis claims due to a double front of his «history battles», on the one hand with the new post Fischer orthodoxy in Western Germany, on the other hand inside of the wide ranging Marxist tradition (especially in the British tradition), and its consolidation in the academic media in the late 1970 was not because of him as a «social historian» but rather as an earlier intermediary between a social history in crisis and an emerging cultural history.
Keywords: German historiography; Geoff Eley; marxist theory; Sonderweg; cultural history